The role of flozins in managing cardiovascular risk in patients with type 2 diabetes - narrative review - Bednarczyk, Paulina; Chodak, Izabella; Chodak, Weronika; Czyczerska, Magdalena; Klimek, Martyna; Lechowski, Sebastian (Quality in Sport, 2024)
Introduction. Cardiovascular disease is a leading cause of morbidity and mortality among patients with type 2 diabetes mellitus. The emergence of flozins, a class of sodium-glucose co-transporter-2 inhibitors, has introduced a novel therapeutic avenue with potential cardiovascular benefits beyond glycemic control. Objective. This review aims to synthesize current evidence on the role of flozins in managing cardiovascular risk among patients with T2DM, examining their efficacy, safety profile, and mechanisms of action. Review methods. A comprehensive literature search was conducted using databases, covering studies published between 2015 and 2024. Clinical trials, meta-analyses, and observational studies evaluating the cardiovascular outcomes associated with flozins in T2DM patients were included. Brief description of the state of knowledge. Research shows that flozins improve glycemic control and provide significant cardiovascular protection, reducing major adverse cardiovascular events, heart failure hospitalizations, and cardiovascular mortality in T2DM patients. These benefits are likely due to hemodynamic changes, enhanced cardiac function, and reduced inflammation and oxidative stress. Summary. Flozins represent a promising therapeutic option for reducing cardiovascular risk in T2DM patients. Their dual benefits on both metabolic and cardiovascular health position them as a cornerstone in the management of T2DM. Further research is needed to fully elucidate their long-term benefits and safety in diverse patient populations.